National Eye Service (1929)
1929 1929 1920s 12 pages [3] NATIONAL EYE SERVICE NATIONAL EYE SERVICE A full list of the addresses in your locality at which this service can be arranged for is given below and overleaf. CENTRAL LONDON 52, Mortimer Street, W.1. 45, Wigmore Street, W.1. 16, Wigmore Street, W.1. 195, Great Portland Street, W.1. 22, Wigmore Street, W.1. 97, Wimpole Street, W.1. 19, Old Bond Street, W.1. 20, Welbeck Street, W.1. 15, Wigmore Street, W.1. 19, Royal Exchange, E.C.3. 50, New Cavendish Street, W.1. 79, Leadenhall Street, E.C.3. 56, New Cavendish Street, W.1. 69A, Duke Street, Grosvenor Square, W.1. 47, Wigmore Street, W.1. 39, Margaret Street, W.1. 14, Sackville Street, W.1. 100, New Bond Street, W.1. 32, Wigmore Street, W.1. 9, Cavendish Square, W.1. 43, New Cavendish Street, W.1 [OVER] 292/841.4/1/61